MORAL CULTIVATION BY WU KANGZHAI: A Mentalism Pioneer in Ming Dynasty - Wang, Jun; Li, Hua; Zou, Jianfeng (Journal of Dharma, 2020)
Wu Kangzhai, an educator in Ming Dynasty of China (AD 1368-1644), expressed his philosophical thoughts through various literary forms such as poetry and journal. An analysis of his works shows that his moral cultivation in different periods reflected his wisdom and sensitivity. However, his theory of moral cultivation and the ‘heart-mind’ duality has been given little to no due attention within the academia. Most scholars regard Wu Kangzai as a scholar of ‘learning of the principle’ rather than a scholar of ‘learning of the heart’. His learning and understanding about ‘heart-mind’ duality may have manifested in his progress of moral practice. This study aims to show Wu’s important role in encouraging learning of the ‘heart-mind’ by Chen Baisha and Wang Yangming. Wu Kangzhai’s learning of the ‘heart-mind’ duality was not only enlightenment and guidance for Wang Yangming’s theory, but also inspired literary schools in Ming Dynasty such as the Tang-Song school, the Gongan school, and later the Ming prose. His observation of self-cultivation and subtle inspection of moral development over the years, parallels the sentimentalism and spiritual writing in the middle and later Ming Dynasty literary works.